TGIF transcription factors repress acetyl CoA metabolic gene expression and promote intestinal tumor growth - Shah, Anant (Genes Dev, 2019)
Tgif1 (thymine–guanine-interacting factor 1) and Tgif2 repress gene expression by binding directly to DNA or interacting with transforming growth factor (TGF) β-responsive SMADs. Tgifs are essential for embryogenesis and may function in tumor progression. By analyzing both gain and loss of Tgif function in a well-established mouse model of intestinal cancer, we show that Tgifs promote adenoma growth in the context of mutant Apc (adenomatous polyposis coli). Despite the tumor-suppressive role of TGFβ signaling, transcriptome profiling of colon tumors suggests minimal effect of Tgifs on the TGFβ pathway. Instead, it appears that Tgifs, which are up-regulated in Apc mutant colon tumors, contribute to reprogramming metabolic gene expression. Integrating gene expression data from colon tumors with other gene expression and chromatin-binding data identifies a set of direct Tgif target genes encoding proteins involved in acetyl CoA and pyruvate metabolism. Analysis of both tumor and nontumor tissues indicates that these genes are targets of Tgif repression in multiple settings, suggesting that this is a core Tgif function. We propose that Tgifs play an important role in regulating basic energy metabolism in normal cells, and that this function of Tgifs is amplified in some cancers.